Skeletal muscle-on-a-chip: an in vitro model to evaluate tissue formation and injury. Issue 20 (5th September 2017) - Agrawal, Gaurav; Aung, Aereas; Varghese, Shyni
Abstract : We introduce a microfluidic platform in which we culture three-dimensional skeletal muscle tissues, while evaluating tissue formation and toxin-induced muscle injury. Abstract : Engineered skeletal muscle tissues can be used for in vitro studies that require physiologically relevant models of native tissues. Herein, we describe the development of a three-dimensional (3D) skeletal muscle tissue that recapitulates the architectural and structural complexities of muscle within a microfluidic device. Using a 3D photo-patterning approach, we spatially confined a cell-laden gelatin network around two bio-inert hydrogel pillars, which induce uniaxial alignment of the cells and serve as anchoring sites for the encapsulated cells and muscle tissues as they form and mature. We have characterized the tissue morphology and strain profile during differentiation of the cells and skeletal muscle tissue formation by using a combination of fluorescence microscopy and computational tools. The time-dependent strain profile suggests the existence of individual cells within the gelatin matrix, which differentiated to form a multinucleated skeletal muscle tissue bundle as a function of culture time. We have also developed a method to calculate the passive tension generated by the engineered muscle tissue bundles suspended between two pillars. Finally, as a proof-of-concept we have examined the applicability of the skeletal muscle-on-chip system as a screening platform and in vitro muscle injury model. We studied the dose-dependent effect of cardiotoxin on the engineered muscle tissue architecture and its subsequent effect on the passive tension. This simple yet effective tool can be appealing for studies that necessitate the analysis of skeletal muscle structure and function, including preclinical drug discovery and development.